The re-co-construction of legitimacy of/through the Doing Business indicators. Issue 4 (3rd January 2018) - Perry-Kessaris, Amanda
Abstract: The present paper argues that the Doing Business indicators, their legitimacy (their ability to be defended through some logic or justification arising from standards) and the wider notions of legitimacy (the standards) that they promulgate are all best understood as social or, better still, 'econosociolegal' constructions. It tracks their, primarily post-financial crisis, re-co-construction within and beyond the World Bank from servant of the private sector and discipliner of states to something approaching social champion. But it warns that the perceptions of legitimacy that have been generated by those indicators may well linger.